PARTNERSHIP DESIGN BETWEEN REGIONAL GOVERNMENTS IN THE EASTERN REGION OF INDONESIA IN SUPPORTING THE DEVELOPMENT OF THE NUSANTARA CAPITAL CITY - Aji Sofyan Effendi; K.P.Suharyono S.Hadiningrat (JIPOWER : Journal of Intellectual Power, 2024)
The relocation of Indonesia’s capital, so called Nusantara, to East Kalimantan Province, has been strengthened formally by the release of Law No. 3/2022, which now is being derived in a Master Plan form for action plan purpose. Currently, initial contructions for Nusantara have been started, which potentially create multiplier efects not only for this province itself but also significant implication on welfare for other 12 provinces in Eastern region of Indonesia (KTI). Design of economic and business cooperation in KTI becomes an obligation that cannot be denied and must be implemented comprehensively so that the backwardness in development between people located in KTI region can be equally achieved as previously experienced by those in KBI region. This article offers design of economic and business cooperation, which enhance policy direction both by the local governments of 12 provinces in KTI and the IKN Authority Agency in order to deal with the relocation of the capital city of the archipelago in East Kalimantan.